Stakeholders of terrorism and the Caribbean: a short case study - Quashie, Emanuel (Palgrave Macmillan, 2023)
The book ambitiously seeks to shape our understanding of terrorism by offering a more systematic interpretation of terrorism-activism through the Stakeholders of Terrorism concept. The author presents an original assessment of terrorism broadly and specifically within the context of the Caribbean through the Stakeholders of Terrorism concept with a view to help the region enhance its counterterrorism policies (nationally & regionally) that recognises the complex inherent duality. In doing so, the author first borrows from and adds to the prevailing literature as it relates to the various explanatory frameworks (psychology, religion, strategy, culture/civilization context, politics and economic dimensions) and the specific stakeholders of terrorism (U.S. mainstream media, ISIS and Individual actors/lone wolf). The Stakeholders of Terrorism concept argues more broadly the existence of an inherent duality, a multiplicity of intangible and tangible negatives and positives that are simultaneously present in most situations concerning terrorism-activism. Emanuel Quashie is Lecturer in the Department of Government at The University of the West Indies, Mona Campus.